2016
DOI: 10.1039/c6cp03058k
|View full text |Cite
|
Sign up to set email alerts
|

Structural origin of proton mobility in a protic ionic liquid/imidazole mixture: insights from computational and experimental results

Abstract: The structure, dynamics, and phase behavior of a binary mixture based on the protic ionic liquid 1-ethylimidazolium bis(trifluoromethanesulfonyl)imide (C2HImTFSI) and imidazole are investigated by (1)H NMR spectroscopy, vibrational spectroscopy, diffusion NMR, calorimetric measurements, and molecular dynamics simulations. Particular attention is given to the nature of the H-bonds established and the consequent occurrence of the Grotthuss mechanism of proton transfer. We find that due to their structural simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 56 publications
5
62
1
Order By: Relevance
“…These demonstrate the formation of cation-base interactions at the expense of existing cation-anion hydrogen-bonding interactions, and are compensated for by the additional imidazolecation interactions. Imidazole-imidazole correlations were not anticipated, but appear consistent with recent work by Yaghini et al 32 where similar results were observed from vibrational spectroscopy and MD simulation.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These demonstrate the formation of cation-base interactions at the expense of existing cation-anion hydrogen-bonding interactions, and are compensated for by the additional imidazolecation interactions. Imidazole-imidazole correlations were not anticipated, but appear consistent with recent work by Yaghini et al 32 where similar results were observed from vibrational spectroscopy and MD simulation.…”
Section: Resultssupporting
confidence: 80%
“…et al 32 have recently studied [1−ethylimidazolium][NTf 2 ] + imidazole mixtures using IR spectroscopy and MD simulation. The results were interpreted in terms of extensive cation-anion, cation-imidazole and imidazole-anion hydrogen-bonding.…”
Section: Yaghinimentioning
confidence: 99%
“…Since crystallization is usually a very slow process in ILs, the dynamic nature of this experiment does not allow a full crystallization of the dense ionic material to take place in the cooling part of the cycle. This cold crystallization after a Tg is typically observed in glass-forming liquids when cooled rapidly enough to prevent crystallization, as it has previously been reported for some based on pyrrolidinium-and methylimidazolium-based ILs [10][11][12][13]. The glass transition is not directly observed here, since EAN's glass transition temperature (previously reported to be -91 ºC [6]) lies clearly below our lowest studied temperature.…”
Section: Chemicalsupporting
confidence: 70%
“…These hydrogen bonding acceptors prefer to coordinate with the hydrogen atoms in the imidazolium rings in the Emim + cations, leading to the formation of multiple hydrogen bonds or a hydrogen bond network within the RTIL matrices. 14,17,21,53 It should be noted that the hydrogen atoms in the imidazolium rings do not coordinate with the F atoms in the NTf 2 − anions via hydrogen bonding interactions due to their lower electronegativities in the anionic framework. However, these hydrogen atoms tend to form hydrogen bonds with the F atoms in the BF 4 − anions but with decreased hydrogen bond directionality and strength.…”
Section: B Comparison Of Dry Bf 4 − and Ntf 2 − Ionic Liquidsmentioning
confidence: 99%
“…Previously, RTIL/water mixtures have been studied using a broad range of methods including optical heterodynedetected optical Kerr effect (OHD-OKE) spectroscopy, 12,14,15 fluorescence spectroscopy, 16 nuclear magnetic resonance spectroscopy, [17][18][19][20][21][22] dielectric spectroscopy, 23 and theoretical and computational calculations. 17,[24][25][26][27][28] In this paper, we use OHD-OKE spectroscopy in conjunction with atomistic molecular dynamic simulations to better understand the interplay between microstructures and dynamics of RTIL/water binary mixtures. New experimental results are combined with previously published data on RTIL/water mixtures to provide a broader understanding of hydrophilicity in RTILs.…”
Section: Introductionmentioning
confidence: 99%